The Role of Digital Ecosystems in Shaping New MSME Business Models - Gerrit Gebrian; Moh. Azhari Zulfani; Lalu Edwin Marjadi P; Andre Satria Dwary; Ayu Nurma Afrilia; Santi Nururly (Postgraduate, University of Mataram, 2026)
The rapid development of digital technology has significantly reshaped the operational landscape of Micro, Small, and Medium Enterprises (MSMEs). This study examines how digital ecosystems comprising e-commerce platforms, social media, digital payment systems, logistics technologies, government support, and online communities shape new business models and enhance MSME competitiveness and sustainability. Using a qualitative descriptive method based on literature review and policy analysis, the study reveals that digitalization enables MSMEs to transform production, marketing, and customer engagement through platform-based business models and digital collaboration networks. Furthermore, it facilitates financial inclusion and opens access to broader national and international markets. However, challenges persist, including limited digital literacy, infrastructural disparities, and unequal access to technology. Addressing these issues requires a synergistic approach involving MSME actors, government institutions, and digital service providers. The findings highlight the strategic role of digital ecosystems not only in fostering innovation and adaptability but also in promoting sustainable business growth for MSMEs in the digital economy era.